Ordered LiNi0.5Mn1.5O4 cathode in bis(fluorosulfonyl)imide-based ionic liquid electrolyte: importance of the cathode–electrolyte interphase - Lee, HJ; Brown, Z; Zhao, Y; Fawdon, J; Song, W; Lee, JH; Ihli, J; Pasta, M (American Chemical Society, 2021)
The high-voltage (4.7 V vs Li+/Li) spinel lithium nickel manganese oxide (LiNi0.5Mn1.5O4, LNMO) is a promising candidate for the next generation of lithium-ion batteries due to its high energy density, low cost, and low environmental impact. However, poor cycling performance at high cutoff potentials limits its commercialization. Herein, hollow-structured LNMO is synergistically paired with an ionic liquid electrolyte, 1 M lithium bis(fluorosulfonyl)imide (LiFSI) in N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide (Pyr1,3FSI), to achieve stable cycling performance and improve the rate capability. The optimized cathode–electrolyte system exhibits extended cycling performance (>85% capacity retention after 300 cycles) and high rate performance (106.2 mAh g–1 at 5C) even at an elevated temperature of 65 °C. X-ray photoelectron spectroscopy and spatially resolved X-ray fluorescence analyses confirm the formation of a robust, LiF-rich cathode–electrolyte interphase. This study presents a comprehensive design strategy to improve the electrochemical performance of high-voltage cathode materials.